A new decavanadate polyoxovanadate nanocluster: synthesis, characterization and rapid adsorption of methylene blue. Issue 17 (2nd September 2017) - Naslhajian, Hadi; Amini, Mojtaba; Farnia, S. Morteza F.; Sheykhi, Ayda; Şahin, Onur; Yeşilel, Okan Zafer
Abstract: A new decavanadate polyoxovanadate nanocluster, [2-ampH]6 [V10 O28 ]∙2H2 O (1 ), was synthesized through reaction between ammonium vanadate and 2-aminopyridine at pH = 2. Nanocluster1 was characterized by IR, elemental analysis, and X-ray crystallography.1 was found to adsorb and desorb dyes and may have widespread application in wastewater treatment. The utility of1 for adsorption of methylene blue was studied. The adsorbed dyes can be easily desorbed, and1 has full efficiency after five cycles. Abstract :